2008
DOI: 10.4103/0970-0218.42057
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of registered visually disabled individuals in a district of West Bengal, India

Abstract: Objective:To identify the sociodemographic characteristics, degree and cause of visual disability among certified visually disabled individuals in a rural district of West Bengal, India and to identify possible lacunae, if any, in the existing certification system.Materials and Methods:A cross-sectional study by secondary data analysis of medical records of 155 visually disabled individuals and their 310 eyes. Demographical features, diagnosis, percentage of visual disability and work activity status of each i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 5 publications
7
21
1
Order By: Relevance
“…9 which observed that 80% of the blind individuals in the rural areas are without any source of income. Similar findings were noted in study by Gosh et al 8 In this study, patients with 100% disability formed the majority group. A similar finding was noted by Kareemsab et al, 6 Gosh et al 8 and Bunce et al 10 Congenital malformations was the leading cause for visual disability in our study followed by retinitis pigmentosa and refractive errors.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…9 which observed that 80% of the blind individuals in the rural areas are without any source of income. Similar findings were noted in study by Gosh et al 8 In this study, patients with 100% disability formed the majority group. A similar finding was noted by Kareemsab et al, 6 Gosh et al 8 and Bunce et al 10 Congenital malformations was the leading cause for visual disability in our study followed by retinitis pigmentosa and refractive errors.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were noted in study by Gosh et al 8 In this study, patients with 100% disability formed the majority group. A similar finding was noted by Kareemsab et al, 6 Gosh et al 8 and Bunce et al 10 Congenital malformations was the leading cause for visual disability in our study followed by retinitis pigmentosa and refractive errors. This is similar to the findings of the study by Kareemsab et al, 6 Ghosh et al 9 The causes were preventable in 41.19% of the patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…They found congenital and developmental anomalies were present in 38.71%. [3] However in our study congenital and developmental anomalities present as high as 55.7% of eyes. Patients with amblyopia, anophthalmos, microcornea, macular dystrophy, microphthalmos, nanophthalmos, retinoblastoma, retinitis pigmentosa, choroidal coloboma were included in congenital and developmental anomaly group.…”
Section: Discussion:-contrasting
confidence: 50%